10 Multilevel factors impacting mammography screening decisions in the elderly: clinician perspectives. (4th December 2019) - Braithwaite, Dejana; Lin, Kenneth; Mishori, Ranit; Schoenborn, Nancy; O'Neill, Suzanne
Abstract : Objectives: Women age 75 and older, who may become accustomed to periodic cancer screening, face difficult decisions when considering whether or not to discontinue screening mammography. A lack of evidence regarding the benefits and harms of screening mammography in U.S. women age 75 and older, which tie to imprecise screening guidelines, leaves women and primary care clinicians with additional uncertainties when it comes to shared decision-making. However, little is known about what clinicians see as most influential in how these decisions are made. The objective of this study was to identify variables that clinicians note as influential in their decision making regarding mammography for women aged 75 and over. Methods: Primary care clinicians who were part of a practice-based research network in the Mid-Atlantic U.S. completed an online, cross-sectional survey in 2019. Participants indicated the degree to which patient, practice and community-level factors influence their decision making regarding mammography for women aged 75 and over (1 = Never influences to 5 = Always influences ). Scores of 4 or 5 were considered influential. Results: Twenty-two out of 122 eligible participants (18%) have completed the survey to date; data collection is ongoing. Participants (Mean age = 51.55 years, 59% female, 73% White) primarily specialized in Family Medicine [17/22, 77.3%]. The mean age at which clinicians reported that they would stop recommending screening mammography was 77.14 years [SD 3.381]. Clinicians were most likely to cite the influence of overall patient comorbidity [19/22, 86.4%], functional status [17/22, 77.3%], and cancer family history [14/22, 63.6%] as factors influencing their decision making process. Additionally, clinicians were influenced by new research regarding screening mammography [17/22, 77.3%] and were more influenced by the U.S. Preventive Services Task Force (USPSTF) guidelines [18/22, 81.8%] than by either American College of Radiology (ACR) [11/22, 50%] and American Cancer Society (ACS) guidelines [11/22, 50%]. Few were impacted by their colleagues [4/22, 18.2%] or policies/norms of their practice setting [4/22, 18.2%]. Approximately half of clinicians indicated that media representations of screening [12/22, 54.5%] and influence of patients' friends and family [10/22, 45.5%] were influential. Conclusions: While our results suggest that decision making and communication about screening mammography in older women are governed primarily by a patient's overall health, scientific evidence, and clinical guidelines that integrate these considerations, prevailing media messages and those close to the patient also play a role. These results underscore the complicated considerations that primary care clinicians face in making recommendations about screening mammography in older women. Acknowledgements: This research was in part supported by grant 1R01CA190841-01A1 from the National Cancer Institute (to Dr. Braithwaite). We thank all study participants and Georgetown-MedStar staff and faculty.